Functional gallic acid-based dendrimers as synthetic nanotools to remodel amyloid-β-42 into noncytotoxic forms - Araújo, Ana Rita Rodrigues (2021)
The self-assembly of amyloid-β (Aβ) generates cytotoxic oligomers linked to the onset and progression of Alzheimer’s disease (AD). As many fundamental molecular pathways that control Aβ aggregation are yet to be unraveled, an important strategy to control Aβ cytotoxicity is the development of bioactive synthetic nanotools capable of interacting with the heterogeneous ensemble of Aβ species and remodel them into noncytotoxic forms. Herein, the synthesis of nanosized, functional gallic acid (Ga)-based dendrimers with a precise number of Ga at their surface is described. It is shown that these Ga-terminated dendrimers interact by H-bonding with monomeric/oligomeric Aβ species at their Glu, Ala, and Asp residues, promoting their remodeling into noncytotoxic aggregates in a process controlled by the Ga units. The multivalent presentation of Ga on the dendrimer surface enhances their ability to interact with Aβ, inhibiting the primary and secondary nucleation of Aβ fibrillization and disrupting the Aβ preformed fibrils.